2005
DOI: 10.1007/s11207-005-1104-8
|View full text |Cite
|
Sign up to set email alerts
|

Very Large Array and SOHO Observations of Type I Noise Storms, Large-Scale Loops and Magnetic Restructuring in the Corona

Abstract: Very Large Array (VLA) observations at 91-cm wavelength are combined with data from the SOHO EIT, MDI and LASCO and used to study the evolving coronal magnetic environment in which Type I noise storms and large-scale coronal loops occur. On one day, we have shown the early evolution of a coronal mass ejection (CME) in projection in the disk by tracing its decimetric continuum emission. The passage of the CME and an associated EUV ejection event coincided with an increase in the 91-cm brightness temperature of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
(7 reference statements)
1
7
0
Order By: Relevance
“…The authors postulated that addition of new material to the corona in the aftermath of a CME leads to reorganization of the local coronal magnetic field, a necessary precondition for the onset of noise storm (Benz & Wentzel 1981;Spicer et al 1981). Similar radio observations in the post-CME period were recently reported by Willson (2005) also through high angular resolution observations with the Very Large Array (VLA). Using the same kind of radio data, Habbal et al (1996) had earlier shown that a type I radio noise storm is limited to the site of a CME despite the existence of a number of active regions on the disk.…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…The authors postulated that addition of new material to the corona in the aftermath of a CME leads to reorganization of the local coronal magnetic field, a necessary precondition for the onset of noise storm (Benz & Wentzel 1981;Spicer et al 1981). Similar radio observations in the post-CME period were recently reported by Willson (2005) also through high angular resolution observations with the Very Large Array (VLA). Using the same kind of radio data, Habbal et al (1996) had earlier shown that a type I radio noise storm is limited to the site of a CME despite the existence of a number of active regions on the disk.…”
Section: Introductionsupporting
confidence: 85%
“…In doing this, we selected only those CME events with central position angle located inside an angular span of ‫54ע‬Њ with respect to the noise storm. We introduced the latter condition because (1) the average width of CMEs observed during the period under study was in the range 47Њ-61Њ (Yashiro et al 2004); (2) CMEs are generally accompanied by a reconfiguration of the magnetic field over extensive regions of the solar atmosphere which in many cases exceeds the CME size (Fainshtein et al 1998;Chertok et al 2001); (3) activity occurring in association with magnetic field changes in the solar atmosphere can be noticed even at an angular distance of ∼30Њ away (Bruzek 1952 (4) the location of a radio noise storm can be close to the footpoint of a CME (Lantos et al 1981;Willson 2005). Figure 1 shows the result of our work.…”
Section: Resultsmentioning
confidence: 99%
“…Despite decades of study, there are a number of unanswered questions about the nature of Type I bursts. Not all active regions that are productive at other wavelengths produce noise storms, and the non-radio signatures are often scant (Willson, 2005;Iwai et al, 2012;Li et al, 2017), unlike Type II and III bursts, which have obvious associations with CMEs and flares (Cairns et al, 2003;Reid and Ratcliffe, 2014). There is general agreement that both the burst and continuum components of noise storms are produced by plasma emission, largely due to their often high circular polarizations (Aschwanden, 1986;Mugundhan et al, 2018), but what accelerates the electrons is still debated.…”
Section: Active Region Noise Storm Sourcesmentioning
confidence: 99%
“…They are associated with active regions, but not directly with flares (for reviews, see Elgarøy 1977;Kai et al 1985;Klein 1998). Noise storm observations were presented by, e.g., Krucker et al (1995) and Malik & Mercier (1996), and their relationship to evolving magnetic structures in the solar atmosphere was discussed in Stewart et al (1986), Raulin & Klein (1994), Bentley et al (2000), and Willson (2005).…”
Section: Introductionmentioning
confidence: 99%